2015
DOI: 10.1161/jaha.114.001530
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐Converting Enzyme‐2 Overexpression Improves Atrial Remodeling and Function in a Canine Model of Atrial Fibrillation

Abstract: BackgroundAtrial fibrosis is an important factor in initiating and maintaining atrial fibrillation. The purpose of this study was to test the hypothesis that atrial angiotensin‐converting enzyme‐2 (ACE2) overexpression might inhibit atrial collagen accumulation and improve atrial remodeling in a canine atrial pacing model.Methods and ResultsThirty‐two mongrel dogs of both genders were divided randomly into 4 groups: sham‐operated, control, gene therapy with adenovirus‐enhanced green fluorescent protein (Ad‐EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Thus the Ca 2+ -permeable TRP channels may serve as potential novel targets for developing anti-fibrotic drugs [ 28 ]. Previous studies demonstrated that the overexpression of ACE2 inhibited myocardial fibrosis [ 29 ]. The results of this study suggest that ACE2 reduces TRPM7 expression, leading to an increase in the atrial tissue ERP, suggesting that ACE2 overexpression mediated by TRPM7 mitigates atrial electrical remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the Ca 2+ -permeable TRP channels may serve as potential novel targets for developing anti-fibrotic drugs [ 28 ]. Previous studies demonstrated that the overexpression of ACE2 inhibited myocardial fibrosis [ 29 ]. The results of this study suggest that ACE2 reduces TRPM7 expression, leading to an increase in the atrial tissue ERP, suggesting that ACE2 overexpression mediated by TRPM7 mitigates atrial electrical remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…The inducibility and duration of AF were measured at basic pacing cycle lengths of 300 ms AF induction was defined as P‐wave disappearance and rapid atrial activation with an irregular ventricular response on an atrial electrocardiogram after atrial programmed stimulation (S1 to S2), which was attempted three times at each site. The duration of induced AF was also recorded …”
Section: Methodsmentioning
confidence: 99%
“…The duration of induced AF was also recorded. 8 Immunohistochemical assays for collagen III and α-SMA were also performed using appropriate antibodies.…”
Section: Electrophysiological Measurementsmentioning
confidence: 99%
See 2 more Smart Citations